A biogeographical analysis of Muhlenbergia (Poaceae: Chloridoideae: Cynodonteae: Muhlenbergiinae). Issue 3 (24th September 2021) - Peterson, Paul M.; Roquet, Cristina; Romaschenko, Konstantin; Herrera Arrieta, Yolanda; Susanna, Alfonso
Abstract: A phylogeny based on the analysis of six DNA sequence markers (ITS, ndhA intron, rpl32‐trnL, rps3, rps16 intron, and rps16‐trnK ) is used to infer ancestral areas and divergence times, and reconstruct the biogeographical history and evolution of 150 of the 183 (82%) species of Muhlenbergia . Our results suggest that the genus originated 9.3 mya in the Sierra Madre (Occidental and Oriental) in Mexico, splitting into six lineages: M. ramulosa diverging 8.2 mya, M . subg. Muhlenbergia at 5.9 mya, M . subg. Pseudosporobolus at 5.9 mya, M . subg. Clomena at 5.4 mya, M . subg. Bealia at 4.3 mya, and M . subg. Trichochloa at 1 mya, each of these with a high probability of Sierra Madrean origin. Our results further suggest that founder‐event speciation from Sierra Madre to South America occurred independently multiple times in all five subgenera during the Pleistocene and late Pliocene. One long‐distance dispersal event most likely originating from Central or Eastern North America to East and Central Asia occurred 1.6–1 mya in M . subg. Muhlenbergia . In our cladogram, members of M . subg. Trichochloa show little genetic resolution, suggesting very low levels of divergence among the species, and this may be a consequence of rapid radiation.